A Influência do descascamento do café cereja orgânico sobre a composição físico-química e sensorial dos grãos - Fernandes, Maria de Fátima Caixeta (2010)
Organic coffee is characterized by being produced without using chemical products and by having grain quality similar or superior to traditional coffee. The non-utilization of highly soluble nutrients sources is one of the factors that guarantee higher value to organic coffee in face of consumers concerned with environmental issues and healthy feeding habits. This paper analyzes the influence of peeling on the quality of organic coffee, in order to present the best way of obtaining high quality coffee. Samples of organic coffee were harvested in both conventional and selective ways, submitted to a peeling process, and treated in a natural way. The samples were then dried on both cement and suspended terraces. The design consisted of eight treatments, having undergone the following analyses: potassium lixiviation; electrical conductivity; titratable acidity; and the coffee cup-test. The results indicated that peeling is feasible for the production of fine coffee. This type of processing effectively influenced the final quality of organic coffee, thus being an alternative, especially for small producers, cooperatives and associations of coffee producers, to improve the quality and value of the product.